Role of NOX2 in the regulation of inflammatory and apoptotic pathways in congolese patients with type 2 diabetes in Brazzaville - Mayassi, Feddercen Kelly Helga; Elenga-Bongo, Charley Loumade; Loubano-Voumbi, Ghislain; Gondo, Juste Brunhel Kaya; Makele, Jeancia Jordanie Mbemba; Bouenizabila, Evariste; Moukassa, Donatien (Frontiers in Endocrinology, 2026)
BackgroundType 2 diabetes (T2D) represents a major global health challenge, characterized by insulin resistance, β-cell dysfunction and chronic inflammation closely linked to reactive oxygen species (ROS) production, particularly through NADPH oxidase 2 (NOX2). Despite advances in understanding oxidative stress mechanisms, the correlation between NOX2 and inflammatory and apoptotic biomarkers remains underexplored in African populations. This study evaluated NOX2’s role in regulating inflammatory and apoptotic pathways in Congolese patients with T2D.MethodsA cross-sectional study (March-June 2024) included 143 T2D patients and 136 controls in Brazzaville. NOX2, inflammatory markers (IL-6, CRP, COX-2), apoptotic markers (Caspase-3), and metabolic parameters (HbA1c, glucose, insulin, C-peptide) were measured using ELISA and Cobas® c111 methods. Relationships between variables were analyzed using Spearman’s correlation test and multiple linear regression, with additional analyses including ANCOVA for treatment comparisons and partial correlations controlling for glycemic control.ResultsNOX2 levels were significantly higher in T2D patients versus controls (20.79 ± 5.14 vs 4.98 ± 1.80 ng/mL, p < 0.001). NOX2 showed positive associations with HbA1c, glucose, and insulin, but demonstrated negative correlations with IL-6 and COX-2. CRP showed no significant correlation with NOX2 (r = +0.04, p = 0.62). Patients with family history exhibited higher NOX2 levels (22.4 vs 19.3 ng/mL, p = 0.002). Multivariate analysis identified HbA1c, BMI, and family history as independent predictors of NOX2 (R² = 0.38). After adjusting for HbA1c, BMI, and diabetes duration, patients on insulin therapy showed significantly higher NOX2 levels compared to those on oral agents alone.ConclusionNOX2 represents an integrative marker associated with metabolic, inflammatory and apoptotic imbalance in T2D. Its elevation in patients with family history and poor glycemic control suggests potential as a risk stratification biomarker, particularly relevant in sub-Saharan Africa where tools for predicting diabetic complications are limited.